The Effect of Trust, Comitment, and SalesPerson Ethical Behavior on Customer Retention: The Mediating Role of Customer Satisfaction: Banking Industry of Thailand - Joemsittiprasert, Watcharin; Siriattakul, Parinya; Jermsittiparsert, Kittisak (International Journal of Psychosocial Rehabilitation, 2019)
The basic purpose to conduct the current research is to find out the impact of sales person ethical behavior, COmitment and trust on customer retention. Moreover, in present studt customer satisfaction is examines as mediator whereas word of mouth as moderatoreThe study is of the view that for the growth and sustainability of organization, satisfaction of customers is very important and a key the better performance of organizations is linked with the satisfaction of the customers. For the organizations to stay alive, it is key that they keep their customers satisfied. The sample technique was cluster sampling used in the survey research. The information is collected from people regarding a specific issue or topic in the survey research method. Questionnaires were distributed through emails among the customers of Thailand Banks. This requires less cost and time and can cover a large geographical region. For the analysis purpose, SEM-PLS is used to conduct the analysis of the variables and test the hypothesis. Whereas, the results of the study has supported the hypothesis. The findings have revealed the fact that positive word of mouth plays a critical role among customers to use the services of the service provider again. Moreover, trust is a significant factor in developing positive image and satisfaction among customers.